TRANSFORMASI PRAKTIK PENGAJARAN GURU SD LABSCHOOL MELALUI PELATIHAN MANAJEMEN KELAS BERBASIS KURIKULUM MERDEKA - Ricky Setiawan; Sujarwanto; Wulan Patria Saroinsong; Nanda Audia Vrisaba; Zeni Zakia Zamania (Transformasi dan Inovasi : Jurnal Pengabdian Masyarakat, 2025)
The implementation of the Merdeka Curriculum at SD LabSchool UNESA since the 2022/2023 academic year has presented new challenges in classroom management and instructional practices. As a reference school for curriculum implementation and teacher development, SD LabSchool UNESA continues to prioritize the enhancement of teacher capacity to create learning environments that are student-centered, adaptive, and conducive. In response to these needs, a classroom management training program was conducted by the Community Service Team (PKM) from the Faculty of Education, Universitas Negeri Surabaya (UNESA). This training aimed to strengthen teachers’ understanding and practical skills in managing classrooms effectively in alignment with the demands of the Merdeka Curriculum. The program consisted of three main phases: material presentation, collaborative group work on designing classroom management strategies, and presentation with facilitator feedback. The training content included student behavior management, classroom layout organization, differentiated instruction approaches, and communication techniques that foster a positive teacher-student relationship. The results indicated a significant improvement in teachers’ ability to design and implement contextually appropriate classroom management strategies. This activity serves as a concrete support effort to reinforce the quality of curriculum implementation at the primary school level.